MEDIAÇÃO NO ENSINO DE CIÊNCIAS (Revista Eletrônica Debates em Educação Científica e Tecnológica, 2022)
Mediational theories emerged in opposition to behaviorist theories of learning and have as structuring conceptions the importance of the subjects of the process, the consideration of the context and a relationship between internal mental activity and cognition. From the analysis of articles in the area of ​​science teaching on didactic activities, a gap was observed in science teaching with regard to the theoretical foundation on pedagogical mediation. In this context, the objective of this work was to reflect on the concept of mediation from the cultural-historical theory, seeking a definition that supports its appropriate use in science teaching. We defend the understanding of mediation as a complex action, which involves social interaction and semiotic mediation. Finally, a reference scheme for a mediated action based on a sequence of contents is proposed for science teaching.